Understanding corporate social responsibility: A survey of Malaysian Muslim managers - Muwazir M.R.; Abdul Hadi N.; Nasohah Z.; Kamri N.A.; Madun A.; Noordin K.; Sarif S.; Yusof M. (2024)
Indexed by Scopus